EFEKTIVITAS KOMUNIKASI PENGGUNAAN APLIKASI ZOOMSEBAGAI MEDIA PEMBELAJARAN ONLINETERHADAP PRESTASI BELAJAR MAHASISWA ILMU KOMUNIKASI UNIVERSITAS RIAU SELAMA PANDEMI COVID-19 - Rola Julianda; Anuar Rasyid (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The current Zoom application is not only a complement to the learning process, but has transformed into the best solution so that it can be said to be one of the needs for achieving effective learning during a pandemic like today. One of the academic activities of users of the Zoom Application is the University of Riau's Communication Studies Students Batch 2018, 2019, and 2020 who activelyuse the Zoom Application. According to CMC (Computer Mediated Communication) Theory, the CMC pattern allows a person to communicate using computer-based communication tools or gadgets supported by internet devices and applications that allow us to carry out various activities virtually such as discussing, reading, watching and accessing required sites. The method used in this research is to use quantitative research methods, and the type of research approach used is descriptive research. The data collection technique is an online questionnaire for Communication Studies Students at the University of Riau class, 2018, 2019 and 2020 as a research population with a total of 609 students and a sample of 85 students obtained through the slovin formula which is determined by purposive sampling technique and tested through the help of the SPSS application . The results of the research hypothesis using the